An unusual geometry of the ionospheric signature of the cusp: implications for magnetopause merging sites - Chisham, G.; Pinnock, M.; Coleman, I. J.; Hairston, M. R.; Walker, A. D. M. (CCSD, 2002)
International audience The HF radar Doppler spectral width boundary (SWB) in the cusp represents a very good proxy for the equatorward edge of cusp ion precipitation in the dayside ionosphere. For intervals where the Interplanetary Magnetic Field (IMF) has a southward component (Bz < 0), the SWB is typically displaced poleward of the actual location of the open-closed field line boundary (or polar cap boundary, PCB). This is due to the poleward motion of newly-reconnected magnetic field lines during the cusp ion travel time from the reconnection X-line to the ionosphere. This paper presents observations of the dayside ionosphere from SuperDARN HF radars in Antarctica during an extended interval ( ~ 12 h) of quasi-steady IMF conditions (By ~ Bz < 0). The observations show a quasi-stationary feature in the SWB in the morning sector close to magnetic local noon which takes the form of a 2° poleward distortion of the boundary. We suggest that two separate reconnection sites exist on the magnetopause at this time, as predicted by the anti-parallel merging hypothesis for these IMF conditions. The observed cusp geometry is a consequence of different ion travel times from the reconnection X-lines to the southern ionosphere on either side of magnetic local noon. These observations provide strong evidence to support the anti-parallel merging hypothesis. This work also shows that mesoscale and small-scale structure in the SWB cannot always be interpreted as reflecting structure in the dayside PCB. Localised variations in the convection flow across the merging gap, or in the ion travel time from the reconnection X-line to the ionosphere, can lead to localised variations in the offset of the SWB from the PCB. These caveats should also be considered when working with other proxies for the dayside PCB which are associated with cusp particle precipitation, such as the 630 nm cusp auroral emission.